PTU-083 Substantial histological improvement following haemopoetic stem cell transplantation. (22nd June 2015) - Sharratt, C; Hawkey, C; Allez, M; Clark, M; Labopin, M; Lindsay, J; Ricart, E; Rogler, G; Satsangi, J; Farge, D; Kaye, P
Abstract : Introduction: Haemopoietic stem cell transplantation (HSCT) leads to complete regression of endoscopic signs of Crohn's disease in about one third of patients, implying an alteration in the natural history of Crohn's disease. We investigated whether these substantial changes were also seen histologically. Method: Patients with impaired quality-of-life from active Crohn's disease not amenable to surgery despite treatment with at least 3 immunosuppressive agents all underwent stem cell mobilisation before randomisation to immuno-ablation followed by unselected cyclophosphamide-based conditioning and HSCT after one month (Early HSCT) or one-year (Delayed HSCT). They underwent full ileocolonoscopy at baseline and after one and two years. Endoscopic involvement and activity were assessed using the Simple Endoscopic Score of Crohn's disease (SES CD) in which a value of zero means no evidence of active or inactive Crohn's disease in any examined segment of the ileum or colon. In 17 patients segments were biopsied systematically for blinded histological assessment, using ECCO-approved scales for intensity and diffuseness of acute and chronic inflammation, granulomas, ulceration, distortion and metaplasia. Results: There was a strong correlation between endoscopic findings and histology (Table 1 ). The % of colonic biopsy samples that were histologically normal rose from 39% (baseline) to 50% at 1 year and 78% at 2 years after Early HSCT (p = 0.039). In patients undergoing Delayed HSCT values were 52% (baseline), 50% 1 year after mobilisation only and 75% after a further year following delayed HSCT (p = 0.329). Improvements were mainly due to reduction or regression of acute and chronic inflammatory changes. Conclusion: Blinded histological assessments fortify the evidence that HSCT can have a profound objective benefit in Crohn's disease. Disclosure of interest: None Declared.